2002
DOI: 10.1364/oe.10.001167
|View full text |Cite
|
Sign up to set email alerts
|

Coherent addition of fiber lasers by use of a fiber coupler

Abstract: Coherent addition of fiber lasers coupled with an intracavity fiber coupler is reported. Almost a single output is obtained from one of the fiber ports, which one can switch simply by unbalancing the losses in the ports. We show that the constructive supermodes, each of which has a single output in a different port, build up automatically because of the dense longitudinal-mode, length-unbalanced laser array with unbalanced port loss. High addition efficiencies of 93.6% for two fiber lasers and 95.6% for four f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(98 citation statements)
references
References 0 publications
2
95
0
1
Order By: Relevance
“…Although the cost estimation of a laser transmitter with 100 MW∼1 GW-output is difficult, the most promising technology for high power output is to coherently couple lasers such as solid, fiber, and diode lasers (Shirakawa et al, 2002;Sanders et al, 1994). The cost of the laser transmitter can be estimated as shown in Table 1 if the coherent coupling is applicable to the array of diode lasers whose production cost per unit of power is currently the cheapest.…”
Section: Launch Costmentioning
confidence: 99%
“…Although the cost estimation of a laser transmitter with 100 MW∼1 GW-output is difficult, the most promising technology for high power output is to coherently couple lasers such as solid, fiber, and diode lasers (Shirakawa et al, 2002;Sanders et al, 1994). The cost of the laser transmitter can be estimated as shown in Table 1 if the coherent coupling is applicable to the array of diode lasers whose production cost per unit of power is currently the cheapest.…”
Section: Launch Costmentioning
confidence: 99%
“…While a sharp transition from no phase locking to full phase locking when the coupling strength exceeds a critical value is predicted, the experimental results revealed a gradual transition, which could be explained by introducing noise to each laser [4,6]. For lasers with many longitudinal modes it was shown that for strong coupling strength only common longitudinal modes survive, leading to full phase locking [7][8][9][10]. Yet, the detailed behavior of phase locking and the spectrum of longitudinal modes as a function of the coupling strength between coupled lasers were so far not reported.…”
mentioning
confidence: 90%
“…Due to high radiation intensities inside a fibre, optical breakdown and nonlinearities are limiting the power extractable from a single fibre laser. A convenient approach to coherent addition of fibre lasers is based on the use of a multi-arm resonator in an interferometer configuration [1][2][3][4][5][6][7][8][9][10]. The coherent combining takes place due to self-organization in laser generation that ensures amplification of resonator modes with the lowest losses.…”
Section: Introductionmentioning
confidence: 99%
“…Michelson and MachZehnder type resonators have been successfully used to reach nearly 100% combining efficiency of two fibre lasers. Coupling was obtained when two amplifying fibres shared a common output mirror located on one port of a standard 50/50 coupler which mixed both optical beams [1][2][3][4][5][6][7][8][9]. When beams of the two input ports of the beam splitter had the correctly fixed relative phase, they interfered constructively at the output port.…”
Section: Introductionmentioning
confidence: 99%